2022
DOI: 10.21037/qims-21-867
|View full text |Cite
|
Sign up to set email alerts
|

The trajectory characteristics and clinical significance of the left-sided lumbar segmental artery: a prospective cross-sectional radio-anatomical study

Abstract: Background: Vascular injury to the lumbar segmental arteries is a devastating complication in minimally invasive lumbar interbody fusion. Previous studies on the anatomy of the lumbar segmental arteries are limited. This prospective cross-sectional study aims to quantitatively describe the brief trajectory of the lumbar segmental arteries on the left side (SegAL) and to discuss its clinical significance.Methods: One hundred and two asymptomatic volunteers were prospectively enrolled and underwent computed tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Thus, the plate length should be limited according to the vascular intervals between the segmental arteries. Our previous study used computed tomography angiography and acquired precise and comprehensive parameters of the segmental arteries (11). We found that the L5 segmental artery was absent in most people, and thus the length of the plates used for L4-5 OLIF could be designed more flexibly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the plate length should be limited according to the vascular intervals between the segmental arteries. Our previous study used computed tomography angiography and acquired precise and comprehensive parameters of the segmental arteries (11). We found that the L5 segmental artery was absent in most people, and thus the length of the plates used for L4-5 OLIF could be designed more flexibly.…”
Section: Discussionmentioning
confidence: 99%
“…To address these issues, the authors completed a series of anatomical studies to acquire the anatomical parameters associated with the plate design for OLIF (11,12). Based on these parameters, we attempted to develop novel and safe lateral plates with an anatomical design.…”
Section: Currently Clinicians Mainly Adopt Two Surgicalmentioning
confidence: 99%
See 1 more Smart Citation
“…We sincerely thank Dr. Pu and his colleagues for their interest and constructive comments on our article. In that paper, novel and safe anatomical lateral plates (ALP) with an anatomical design based on the parameters acquired in our previous studies were developed ( 1 , 2 ). The initial design was introduced and its biomechanical performance was verified with the comparison of various internal fixations.…”
mentioning
confidence: 99%